Relationship (Correlation) between BruininksOseretsky Test of Motor Proficiency and Peabody Developmental Motor Scale on Children with Educable-Intellectual and Developmental Disabilities - Kobra Soltanikhadiv; Mohamad Kamali; Shahla Rafiei; Ghorban Taghizade (Vesnu Publications, 2014)
Abstract Background and Purpose: Children with Intellectual and Developmental Disabilities (IDD) have deficits or limitations in motor function. So identification and assessment of motor problems in preschool age children for suitable intervention is essential. The purpose of this study was to determine if there was a correlation between BruininksOseretsky Test of Motor Proficiency (BOTMP) and Peabody Developmental Motor Scale - second edition (PDMS2) on children with IDD. Methods: Subjects were 60 children with IDD at 54-83 months of age who their motor skills (gross, fine) were assessed with BOTMP and PDMS2. Results:The results indicated that there was moderate to high correlation between the two motor tests composite scores(r= 0/65-0/91),gross motor scores (0/58-0/88) .and fine motor scores( 0/60-0/88). Conclusion: Considering the moderate to high correlation between BOTMP and PDMS2, therapists can use one of these tests to assess motor skill of children. Considering the test's Items number and Time, BOTMP seems better than PDMS2 for this group of children. Key words: BOTMP , PDMS2, Intellectual  Disability, Motor Skills